Daya Simpan Dan Kualitas Telur Ayam Ras Dilapisi Minyak Kelapa, Kapur Sirih Dan Ekstrak Etanol Kelopak Rosella - Ari Hepi Yanti, Suci Rahmawati, Tri Rima Setyawati (Universitas Tanjungpura, 2014)
Chicken egg is one of cattles products which is easily damaged if it is stored more than 14 days. This research aimed to determine the ability of coconut oil, the solution of slaked lime and ethanol extract of Hibiscus sabdariffa as well as the optimal combination of these materials in maintaining the quality of eggs during storage. This study used a Completely Randomized Design (CRD) with seven treatments and three replications. There were 27 eggs used in this study which were stored for 30 days. Each treatment had no effect on egg shell color, except the color of the egg shell coated with solution of slaked lime. Treatment that provided optimal result was the combination of coconut oil, solution of slaked lime and ethanol extract of Hibiscus sabdariffa (K7) with the decrease of egg weight, acidity, white and yellow indices as well as Haugh unit by 2,88%, 8,1, 0,067, 0,350 and 78 respectively in a 30 day storage period.